High-gloss spraying-free PC / ABS material and preparation method thereof
By adding polystyrene latex to high-gloss spray-free PC/ABS materials, the problem of welding and dark hair in places where the product has many structural characteristics and flow convergence is solved, and the good dispersion of the upper gloss pigment and the material's scratch resistance is achieved, and the high-quality and scratch resistance standards of the automotive industry are met.
Patent Information
- Application Number
- CN202411416937.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-25
AI Technical Summary
The existing high-gloss spray-free PC/ABS materials are prone to fusion darkening in places where the product has many structural characteristics and flow convergence, forming flow marks and welded wires, and have poor scratch resistance, which cannot meet the high-quality and scratch resistance standards of the automotive industry.
Polystyrene latex is added as a supplementary dispersant to the formulation of high-gloss spray-free PC/ABS material, and blended and granulated through a twin-screw extruder to improve the dispersion of the glossy pigment and the scratch resistance of the material.
It effectively avoids the accumulation of glossy pigments, reduces the occurrence of flow marks and welded wires, improves the scratch resistance of the material, and meets the requirements of the automotive industry for high-quality parts.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a high-gloss spray-free PC / ABS material and a preparation method thereof. Background Art
[0002] As people pay more attention to the energy crisis, energy conservation and emission reduction of automobiles are the development requirements of today's automobile industry. Among them, lightweighting of automobiles and "replacing steel with plastics" have become important development directions of today's automobile industry, thus providing a good opportunity for the development of the plastics industry. At the same time, the requirements for plastics performance are getting higher and higher.
[0003] In order to achieve a high gloss effect on some parts of the car, the usual practice is to spray high gloss paint on the plastic substrate, but spraying paint not only has high processing costs, but is also not environmentally friendly. With the introduction of the ELV law for automobiles, more thermoplastic materials need to be directly recycled without the need to separate the thermosetting paint film. Therefore, it is of great significance to research and develop materials that do not require spraying.
[0004] PC / ABS is a thermoplastic plastic made of polycarbonate (PC) and acrylonitrile-butadiene-styrene copolymer (ABS) alloy. As a spray-free environmentally friendly green material, it has been widely used in the home appliance industry, but its application in the automotive industry is still in the development stage. The high gloss effect of spray-free on PC / ABS materials is mainly achieved by adding gloss pigments to PC / ABS materials. Gloss pigments, such as metallic pigments or pearlescent pigments, have shear sensitivity, orientation and accumulation problems. Dark welds will appear in places where there are more structural features of the product and where the flow converges. It is easy to form defects such as flow marks and weld lines on the surface of the product, which cannot meet the requirements of high-quality products and limits its large-scale application in the automotive industry.
[0005] In addition, the scratch resistance of high-gloss spray-free PC / ABS is poor, which cannot be compared with the scratch resistance of painted parts, and cannot meet the automotive industry's scratch resistance standards for parts, which also limits its application in automobiles. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a high-gloss spray-free PC / ABS material, characterized in that it comprises the following raw materials in parts by weight: 60-70 parts of PC, 10-30 parts of ABS, 0-5 parts of metal powder or pearl powder, 0.1-1 parts of compatibilizer, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of lubricant, 0.2-0.5 parts of antioxidant and 0.5-2 parts of light stabilizer, wherein the dispersant is polystyrene latex.
[0007] Furthermore, the polystyrene latex is prepared as follows: a reaction suspension containing 15-35 wt% of styrene monomer, 0.2-2.5 wt% of a dispersant and the balance being water is prepared, and the suspension is heated to perform a polymerization reaction.
[0008] Furthermore, 0-3.5 wt % of a free radical initiator selected from azobisisobutyronitrile or ditoluoyl peroxide may be added to the reaction suspension.
[0009] Furthermore, the polymerization reaction is carried out at 80-90° C. for 6-12 hours.
[0010] Furthermore, the dispersant is selected from at least one of sodium stearate, sodium lauryl sulfate, sodium lauryl sulfonate, and zinc dialkyl dithiophosphate.
[0011] Furthermore, the dispersant is a mixture of sodium stearate, sodium lauryl sulfate or sodium lauryl sulfonate and dialkyl zinc dithiophosphate.
[0012] Furthermore, the particle size of polystyrene in the polystyrene latex is 1-10 μm.
[0013] Furthermore, the water may be distilled water or deionized water.
[0014] Furthermore, the specific preparation process of the polystyrene latex can be carried out as follows: a certain amount of styrene, water and dispersant are mixed, a stable suspension is obtained by electromagnetic stirring or mechanical stirring or ultrasonic emulsification, a free radical initiator is selectively added, and the mixture is heated to 50-90° C. under nitrogen protection to carry out polymerization reaction for 6-12 hours. After the reaction is completed, a small amount of polymer precipitate that may be generated is filtered out to obtain a polymer latex.
[0015] Furthermore, the particle size of the metal powder or pearl powder is 2-150 μm. The metal powder can be aluminum powder, silver powder, copper powder, etc., and the pearl powder can be natural pearl powder, mica pearl powder, etc. Adding metal powder or mica powder can make the material have a metallic texture, high gloss and a visual sense of a glittering effect. The content and particle size of the added metal powder or pearl powder are different, and the effect varies, from a delicate metallic texture to a metallic glittering effect, which can be achieved by adjusting the amount and particle size of the metal powder or pearl powder.
[0016] Furthermore, the melt index of PC is 10-30 g / 10 min at 300° C. / 1.2 KG.
[0017] Furthermore, the ABS is an ABS resin synthesized by a bulk method and having a rubber content of 15%-25%.
[0018] Furthermore, the compatibilizer is a SAN-g-GMA copolymer, wherein the weight percentage of GMA is 1-8%.
[0019] Furthermore, the lubricant is at least one of liquid paraffin, solid paraffin, silane polymer, fatty acid salt, stearic acid amide, calcium stearate, zinc stearate, methylene bisstearic acid amide and N,N-ethylene bisstearic acid amide.
[0020] Furthermore, the antioxidant is at least one of hindered phenols and phosphite antioxidants; specifically, the antioxidant is at least one of antioxidants 168, 264, 1010, 1076, and 1098; more specifically, the antioxidant is a composite antioxidant composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.
[0021] Furthermore, the light stabilizer is a benzotriazole light stabilizer and / or a hindered amine light stabilizer.
[0022] The present invention also provides a method for preparing the high-gloss spray-free PC / ABS material as described herein, which comprises the following steps:
[0023] Add required weight portions of PC, ABS, metal powder or pearl powder, compatibilizer, dispersant, lubricant, antioxidant and light stabilizer into a mixing mixer and mix uniformly to obtain a mixture;
[0024] The mixture is blended and granulated by a twin-screw extruder to obtain a high-gloss spray-free PC / ABS material.
[0025] Furthermore, the screw temperature of the twin-screw extruder is in the range of 220-280° C., and the screw speed is in the range of 300-600 rpm.
[0026] Beneficial effects of the present invention
[0027] In order to improve the dispersibility of the glossing pigment and the scratch resistance of the PC / ABS material, the present invention adds polystyrene latex to the traditional formula of the high-gloss spray-free PC / ABS material, which can act as a coating agent to encapsulate the glossing pigment, so that the glossing pigment can be well dispersed in the PC / ABS material to avoid accumulation. In addition, the present invention also finds that polystyrene latex can give the PC / ABS material better scratch resistance. When polystyrene is used to replace polystyrene latex, the scratch resistance of the PC / ABS material cannot be improved. DETAILED DESCRIPTION
[0028] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0029] The PC used in the examples was purchased from Shanghai Petrochemical, and under the test conditions of GB / T 3682-2000, 300°C / 1.2KG, the melt index was 25g / 10min;
[0030] ABS is synthesized by bulk method, with a rubber content of 15%-25%;
[0031] The compatibilizer SAN-g-GMA uses SAG-005 from Nantong Rizhisheng;
[0032] The light stabilizer is a 1:1 mixture of a benzotriazole light stabilizer (brand name TINUVIN 234, purchased from BASF) and a hindered amine light stabilizer (brand name Uvinul 5050H, purchased from BASF).
[0033] Example 1
[0034] The present embodiment provides a high-gloss spray-free PC / ABS material, which includes the following raw materials in parts by weight: 70 parts of PC, 20 parts of ABS, 4 parts of natural pearl powder, 0.5 parts of SAN-g-GMA, 0.5 parts of dispersant, 0.5 parts of methylene bisstearamide, 0.5 parts of antioxidant (a composite antioxidant composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) and 1 part of light stabilizer.
[0035] The dispersant is polystyrene latex, which is prepared as follows: 20 mL of styrene, 80 mL of distilled water, 300 mg of sodium stearate and 200 mg of zinc dialkyl dithiophosphate are mixed, and under nitrogen protection, electromagnetic stirring is performed for 45 minutes to obtain a white stable suspension, 20 mL of an aqueous solution containing 100 mg of ditoluyl peroxide is added to the suspension, the water bath is heated to 85° C., and the reaction is stirred at a constant temperature for 8 hours, and a small amount of polymer precipitate is filtered to remove, so as to obtain a polystyrene latex product with a solid content of 14.9%.
[0036] The high gloss spray-free PC / ABS material is prepared as follows:
[0037] Add the weight proportions of PC, ABS, natural pearl powder, SAN-g-GMA, polystyrene latex, methylene bisstearic acid amide, antioxidant and light stabilizer into a mixing blender and mix evenly to obtain a mixture;
[0038] The mixture is melt-extruded, granulated and dried through a twin-screw extruder to obtain the high-gloss spray-free PC / ABS material, wherein the barrel temperature range of the twin-screw extruder is 220-280° C., and the screw speed is 500 rpm.
[0039] Example 2
[0040] The present embodiment provides a high-gloss spray-free PC / ABS material, which includes the following raw materials in parts by weight: 65 parts of PC, 10 parts of ABS, 4 parts of silver powder, 0.5 parts of SAN-g-GMA, 0.5 parts of dispersant, 0.5 parts of zinc stearate, 0.5 parts of antioxidant (a composite antioxidant composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) and 1 part of light stabilizer.
[0041] The dispersant is polystyrene latex, which is prepared as follows: 20 mL of styrene, 80 mL of distilled water, 200 mg of sodium dodecyl sulfate and 200 mg of zinc dialkyl dithiophosphate are mixed, and under nitrogen protection, electromagnetic stirring is performed for 45 minutes to obtain a white stable suspension, 20 mL of an aqueous solution containing 100 mg of ditoluyl peroxide is added to the suspension, the water bath is heated to 85° C., and the reaction is stirred at a constant temperature for 8 hours, and a small amount of polymer precipitate is filtered to remove, so as to obtain a polystyrene latex product with a solid content of 15.2%.
[0042] The high gloss spray-free PC / ABS material is prepared as follows:
[0043] Add the weight proportions of PC, ABS, natural pearl powder, SAN-g-GMA, polystyrene latex, methylene bisstearic acid amide, antioxidant and light stabilizer into a mixing blender and mix evenly to obtain a mixture;
[0044] The mixture is melt-extruded, granulated and dried through a twin-screw extruder to obtain the high-gloss spray-free PC / ABS material, wherein the barrel temperature range of the twin-screw extruder is 220-280° C., and the screw speed is 400 rpm.
[0045] Example 3
[0046] The present embodiment provides a high-gloss spray-free PC / ABS material, which includes the following raw materials in parts by weight: 60 parts of PC, 30 parts of ABS, 1 part of natural pearl powder, 0.5 parts of SAN-g-GMA, 0.3 parts of dispersant, 0.3 parts of methylene bisstearamide, 0.5 parts of antioxidant (a composite antioxidant composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1) and 1 part of light stabilizer.
[0047] The dispersant is polystyrene latex, which is prepared as follows: 20 mL of styrene, 80 mL of distilled water, 200 mg of sodium stearate and 300 mg of zinc dialkyl dithiophosphate are mixed, and under nitrogen protection, electromagnetic stirring is performed for 45 minutes to obtain a white stable suspension, 20 mL of an aqueous solution containing 100 mg of ditoluyl peroxide is added to the suspension, the water bath is heated to 85° C., and the reaction is stirred at a constant temperature for 8 hours, and a small amount of polymer precipitate is filtered to remove, so as to obtain a polystyrene latex product with a solid content of 14.5%.
[0048] The high gloss spray-free PC / ABS material is prepared as follows:
[0049] Add the weight proportions of PC, ABS, natural pearl powder, SAN-g-GMA, polystyrene latex, methylene bisstearic acid amide, antioxidant and light stabilizer into a mixing blender and mix evenly to obtain a mixture;
[0050] The mixture is melt-extruded, granulated and dried through a twin-screw extruder to obtain the high-gloss spray-free PC / ABS material, wherein the barrel temperature range of the twin-screw extruder is 220-280° C., and the screw speed is 500 rpm.
[0051] Comparative Example 1
[0052] This comparative example provides a PC / ABS material, which differs from the high-gloss spray-free PC / ABS material of Example 1 in that it does not contain the dispersant polystyrene latex, and the remaining components and preparation method are the same as those of Example 1.
[0053] Comparative Example 2
[0054] This comparative example provides a PC / ABS material, which is different from the high-gloss spray-free PC / ABS material of Example 1 in that it does not contain a lubricant, namely, methylene bisstearamide, and the remaining components and preparation method are the same as those of Example 1.
[0055] Comparative Example 3
[0056] This comparative example provides a PC / ABS material, which is different from the high-gloss spray-free PC / ABS material of Example 1 in that polystyrene is used instead of polystyrene latex, and the remaining components and preparation method are the same as those of Example 1.
[0057] Comparative Example 4
[0058] This comparative example provides a PC / ABS material, which differs from the high-gloss spray-free PC / ABS material of Example 1 in that silicone gel is used as a coating agent instead of polystyrene latex, and the remaining components and preparation method are the same as those of Example 1.
[0059] The PC / ABS materials prepared in the above Examples 1-3 and Comparative Examples 1-4 were injection molded into high-gloss boards, and the presence of flow marks and weld lines on the surface and the pencil hardness thereof were evaluated. The results are shown in Table 1.
[0060] Table 1
[0061]
[0062]
[0063] Note: - means there is no flow mark or weld line, or it is not obvious; more + means more flow marks; more ° means more serious weld line.
[0064] From the results in Table 1, it can be seen that, compared with the PC / ABS material without polystyrene latex (Comparative Example 1), the PC / ABS material with polystyrene latex added has basically no flow marks and weld lines on the surface, and has good scratch resistance; when only polystyrene latex is contained without lubricant (Comparative Example 2), although the PC / ABS material of polystyrene latex has good surface hardness, there are more flow marks and weld lines on the surface of the material, which shows that the single polystyrene latex is not effective in improving the gloss pigment and dispersibility problems of the gloss pigment; when polystyrene is used to replace polystyrene latex (Comparative Example 3), the surface flow marks, weld lines and pencil hardness of the PC / ABS material are not improved, which shows the indispensability of the polystyrene latex prepared by the present invention; when a coating agent is used to replace polystyrene latex (Comparative Example 4), it can be seen that the surface flow marks and weld lines of the PC / ABS material are improved, but the scratch resistance is poor.
[0065] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.
Claims
1. A high gloss spray-free PC / ABS material, characterized in that: The following raw materials are included by weight: 60-70 parts of PC, 10-30 parts of ABS, 0-5 parts of metal powder or pearl powder, 0.1-1 parts of compatibilizer, 0.1-0.5 parts of dispersant, 0.1-0.5 parts of lubricant, 0.2-0.5 parts of antioxidant and 0.5-2 parts of light stabilizer. The dispersant is polystyrene latex.
2. The high gloss spray-free PC / ABS material according to claim 1, characterized in that: The polystyrene latex is prepared as follows: a reaction suspension containing 15-35 wt% of styrene monomer, 0.2-2.5 wt% of a dispersant and the balance of water is prepared, and the suspension is heated to carry out a polymerization reaction.
3. The high gloss spray-free PC / ABS material according to claim 2, characterized in that: 0-3.5 wt % of a free radical initiator selected from azobisisobutyronitrile or ditoluoyl peroxide may also be added to the reaction suspension.
4. The high gloss spray-free PC / ABS material according to claim 2, characterized in that: The polymerization reaction is carried out at 80-90°C for 6-12 hours.
5. The high gloss spray-free PC / ABS material according to claim 2, characterized in that: The dispersant is selected from at least one of sodium stearate, sodium lauryl sulfate, sodium lauryl sulfonate, and zinc dialkyl dithiophosphate; Preferably, the dispersant is sodium stearate, sodium lauryl sulfate or a mixture of sodium lauryl sulfonate and zinc dialkyl dithiophosphate.
6. The high gloss spray-free PC / ABS material according to claim 1, characterized in that: The particle size of the metal powder or pearl powder is 2-150 μm.
7. The high gloss spray-free PC / ABS material according to claim 1, characterized in that: The compatibilizer is a SAN-g-GMA copolymer, wherein the weight percentage of GMA is 1-8%.
8. The high gloss spray-free PC / ABS material according to claim 1, characterized in that: The lubricant is at least one of liquid paraffin, solid paraffin, silane polymer, fatty acid salt, stearic acid amide, calcium stearate, zinc stearate, methylene bis stearic acid amide and N,N-ethylene bis stearic acid amide.
9. The high-gloss spray-free PC / ABS material according to claim 1, wherein the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant; The light stabilizer is a benzotriazole light stabilizer and / or a hindered amine light stabilizer.
10. A method for preparing a high gloss spray-free PC / ABS material according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add required weight portions of PC, ABS, metal powder or pearl powder, compatibilizer, dispersant, lubricant, antioxidant and light stabilizer into a mixing mixer and mix uniformly to obtain a mixture; The mixture is blended and granulated by a twin-screw extruder to obtain a high-gloss spray-free PC / ABS material; Furthermore, the screw temperature of the twin-screw extruder is in the range of 220-280° C., and the screw speed is in the range of 300-600 rpm.